Undersökning av självspridning av contortatallen i norra Sverige - Sjödin, Jonas (SLU/Dept. of Forest Ecology and Management, 2012)
Over the past 40 years 600 000 ha of lodgepole pine (Pinus contorta ssp. latifolia (Engelm.) Critchf.) has been planted in Sweden (280 000 ha on SCA's forest land alone which represents about 15% of the company's total forest land area). In the early 70's SCA situated a number of experimental stands in order to investigate different aspects of the exotic tree, primarily growth rate. To be able to compare the two species plots with scots pine (Pinus sylvestris L.), this species was also planted at the same time and under the same conditions. A number of questions should always be raised when exotic species are introduced in an ecosystem. Invasiveness, the pathogen situation and purely ethical issues should be discussed. One of the limiting factors of the lodgepole pine's invasiveness is its serotinous cones. Nevertheless has a certain self-spread still been shown to occur in the Swedish forest. The serotinous cones of the lodgepole pine are an evolutionary adaption to forest fire. In these cones it accumulates a great number of seeds in order to be released after the next fire. In addition to these cones there are a few cones that are able to spread the seed without heat. This makes the culture populations of lodgepole pine and their close environment is subjected to continuous exposure of viable seeds. The intention of this report is to investigate the potential of self-spread and establishment of P. contorta beyond the bounds of the cultural stands in northern Sweden. The establishment ability of the lodgepole pine is influenced by several habitat characteristics (such as vegetation, altitude, latitude, soil moisture). In the autumn of 2011 a field study was conducted with the intention of collecting suitable data in order to analyze these characteristics. The studies were carried out on 20 of SCA's trial facilities. These are located between 120-510 meters above sea level and in the range of 62° 12' N and 66° 11' N. Similar studies were carried out in 2000 and those results gave the opportunity to a comparison ...